Strategy making: strategic initiative implementation in the context of renewing a firm's sources of competitive advantage - Kovacic, Wladimir (2008)
Strategic initiative implementation has evolved in recent years as a new and progressive form of strategy making. In this regard, strategic initiative implementation constitutes one of the central topics of strategic management regarding how firms can renew their most valuable sources of competitive advantage: the firm's idiosyncratic resources and knowledge base.